Florence Nightingale's Nursing and Health Care: The Worldwide Legacy, As Seen on the Bicentenary of Her Birth - Lynn McDonald (Ital Publication, 2021)
Aim: The aim of this article is to articulate the distinctive features on the Nightingale School of Nursing on the occasion of the 2020 bicentenary of her birth. Design: This is a historical study, based on all the available printed and archival sources of Nightingale's writing. Methods: The article draws on Nightingale sources (full books, articles, chapters, pamphlets and unpublished letters in more than 200 libraries and archives worldwide) published in The Collected Works of Florence Nightingale, 16 volumes, peer-reviewed; transcriptions are available on its website [1]. Results: Nine key findings are discussed in the article: (1) how different Nightingale's nursing was from what was called 'nursing' at the time; (2) that the central role of training allowed nursing to move from being a women's profession to being open to all qualified; (3) the evolution of Nightingale nursing as medical science and public health advanced; (4) the academic content in her training; (5) team building in her system; (6) her (often misrepresented) views on germ theory; (7) her late work on preventing cholera; (8) the worldwide influence of her work; (9) her work upgrading workhouse infirmaries and advocacy of what would be later called universal access to health care. Conclusion: Nightingale's ongoing relevance is evident in many of today's concerns, such as lack of access to quality health care; the shortage of nurses in the United Kingdom's National Health Service (and in some other countries) and inadequate wages and salaries of nurses and nurse practitioners; the ongoing dangers in nursing and the need to give nurses a safe working environment (the coronavirus is an extreme example); and inadequate data for health care planning purposes.   Doi: 10.28991/SciMedJ-2021-0301-7 Full Text: PDF